(untitled) (Stamford Journal of Microbiology, 2022)
When healthcare professionals handle infected materials with their hands and gloves or when patients come into contact with contaminated surfaces directly, environmental contamination enhances the transmission of bacteria. This study aimed to determine the antimicrobial resistance of bacteria isolated from high-touched surfaces in Madonna Catholic hospital, Abia State. Samples of the most commonly contacted surfaces were gathered by rubbing and spinning sterile swabs sticks with normal saline on the surfaces. Direct inoculation of the swab samples using the streak plate method was done on Blood agar and MacConkey agar plates. The serial dilution method enumerated the bacterial species associated with the contact surfaces. The bacterial isolates were subjected to an antibiotic susceptibility test using the Kirby Bauer disc diffusion technique. This study showed that thirty-six (36) bacteria isolates were obtained from fifty (50) swab samples collected from high-touched surfaces. It was also observed that Staphylococcus aureus is the most frequently occurring isolate with 12 (33.3%), followed by coagulase- negative Staphylococci 10 (27.8%). The least occurring isolate was recorded for Pseudomonas spp. 5 (13.9%). It was recorded in this study that door handles showed the highest distribution of bacterial isolates 14 (38.8%), whereas swab samples obtained from the benches showed a minor distribution 2 (5.5%). However, the antibiotics susceptibility profile of bacterial isolate from the sampled surfaces showed that Ciprofloxacin was the most effective antibiotic tested at a rate of 100%. It was revealed in this study that most of the bacterial isolates showed a highest level of resistance to Chloramphenicol, Tetracycline and Ampiclox (100%). An appreciable number of pathogenic bacteria isolates were detected in the frequently touched surfaces in the hospital. The presence of these organisms could be the leading cause of hospital-acquired infections. Suitable hygienic measures must be adopted at the hospital to reduce the level of contamination and spread of disease through these surfaces. It is also vital to promote excellent personal hygiene like hand washing. This study finding suggests that ciprofloxacin can be used for treatment and control bacterial infections. Stamford Journal of Microbiology, Vol.12 (1) 2022: 1-7